Al-Fi’il al-Ṡulāṡī al-Muta’addī Fī Film Kartūn “al-Qiṭ al-Ḍāi’” - Laely Yuliani Said; Limpo, Marwah; Fitriani; Abidin, Zaenal (Al-Hikmah Journal for Religious Studies, 2024)
Abstract This study discusses about fi'il ṡulāṡī muta'addī (transitive verb) used in the cartoon film "al-Qiṭ al-Ḍāi'". The aim is to find out the division and i'rāb of the transitive verb (consisting of three letters) used in the film. The research method used by researchers in this study is a descriptive qualitative method by looking at various books and articles related to this study. The primary sources used are the cartoon film "al-Qiṭ al-Ḍāi'", and the secondary sources used are references derived from nahwu and sharf books, articles, and others. The study found that the fi'il ṡulāṡī muta'addī used in the cartoon film "al-Qiṭ al-Ḍāi'" totaled 128 verbs consisting of two types of verbs, namely fi'il mujarrad (verbs composed of the original three letters) and fi'il mazīd (verbs with additional letters entered). There are 73 fi'il mujarrad and 55 fi'il mazīd. Both types of verbs are muta'addi by themselves, and some need harf al-jar in order to add maf'ūl (object). This research is expected to deepen insight and knowledge about fi'il ṡulāṡī muta'addī (transitive verb) analysis of literary works, especially for researchers and readers in general. Keywords: Transitive Verb, The Cartoon Film, al-Qiṭ al-Ḍāi'